Detection of Human Influenza A Viruses by Loop-Mediated Isothermal Amplification - Poon, Leo L. M. (American Society for Microbiology, 2005)
Here we describe the use of the loop-mediated isothermal amplification (LAMP) method to detect human influenza viruses (H1 to H3). Our results were correlated 100% with results deduced from routine clinical diagnostic tests. In addition, we also developed a LAMP assay specific for human β-actin cDNA as a quality control test.